STRATEGIC APPROACH TO FORMATION THE MOTIVATION SECURITY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. The analysis of scientific sources showed that the issues of staff motivation are considered as a solution of the tactical level, with which we can agree. But in our opinion, ensuring of motivational security should be reflected as a strategic vision. However, the issues of motivational security are rarely violated by scientists, so they remain practically not studied and require further research.The purpose of the article. The purpose of the paper is to highlight the problem of strategic approach to ensuring of motivational security. In accordance with the stated goal, the task of the research: to reveal the essence of motivational security; develop strategies of providing the motivational security.Results. The article deals with the approaches of scientists to the structural filling of motivational security and its content definition. On the basis of generalizations and assumptions, the author's interpretation of motivational security was formulated and components of motivational security were determined. In particular, motivational security should include material, career, labor, socio-psychological and pension-insurance security. An explanation of each component of motivational security is given.The steps of the process of strategic providing the motivational security are determined. It is determined that a strategic approach to managing the process of providing the motivational security include the following steps: gathering information about the enterprise's motivational policy, its effectiveness and the current level of motivational security; identification the factors of influence, risks and threats to motivational security; assessment of the level of impact of identified risks and threats on motivational security; assessment of the enterprise's capabilities to providing the motivational security; choosing a strategy for ensuring motivational of security; implementation the strategy; monitoring the process of strategy implementation and making adjustments if necessary; evaluation of the results of the strategy implementation and formulation conclusions and recommendations for the future.Motivational security strategies have been developed. Considering the current level of motivational security and the available capabilities of the company to provide it, the following strategies are outlined: a growth strategy that can be implemented as an integrated, combined or selective growth strategy; position retention strategy, which is divided into active and passive; a coordination strategy that can be object-oriented or subject-oriented; self-regulation strategy.Conclusiоns. The scientific novelty of the research is to determine the essence of motivational security, its structural content, stages of strategic support and appropriate strategies.
Keywords: security, motivational security, social security, personnel security, motivation, stimulation, strategy